2010
DOI: 10.1680/geot.8.p.094
|View full text |Cite
|
Sign up to set email alerts
|

A shear-displacement criterion for soil-infilled rock discontinuities

Abstract: Dans une masse rocheuse, un joint rocheux rempli est probablement le plan le plus faible. L'effet le plus saillant de la présence de matières de remplissage est la réduction du frottement dans les limites de discontinuité (autrement dit le contact entre une roche et l'autre de parois conjointes). Plus la matière de remplissage est épaisse, moins la résistance au cisaillement du joint rocheux est élevée. Lorsque la matière de remplissage atteint une épaisseur critique, les parois conjointes (roche) ne jouent pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 11 publications
0
28
0
2
Order By: Relevance
“…The changes in the macroscopic mechanical characteristics result from changes in the microstructure (Indraratna et al, 2010;Liu and Xu, 2014;Wu et al, 2013). Rocks in practical engineering are generally subjected to joint action of two or more factors.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the macroscopic mechanical characteristics result from changes in the microstructure (Indraratna et al, 2010;Liu and Xu, 2014;Wu et al, 2013). Rocks in practical engineering are generally subjected to joint action of two or more factors.…”
Section: Discussionmentioning
confidence: 99%
“…ese soft fillings significantly weaken the shear strength of jointed rock and make the rock present more obvious heterogeneity and anisotropy. Infilled joints generally become the weakest position under shear which will easily trigger the whole instability of engineering rock [1][2][3][4]. erefore, the study of shear properties of infilled joints is of significance in both stability evaluation and reinforcement of engineering rock.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the in lled ratio, that is, the ratio of lling thickness, t, and the asperity height, a, is a signi cant factor controlling the shear properties of in lled joints. A large number of direct shear test results [1,3,[12][13][14][15][16] showed that the in lled ratio, t/a, has a critical value. If the in lled ratio is less than the critical value, the shear failure strength of in lled joints is typically higher than the shear strength of llings but lower than that of asperity.…”
Section: Introductionmentioning
confidence: 99%
“…These discontinuities largely weaken the overall stability of rock masses (Barton 1974), which is one of the largest concerns in mining and civil engineering. Factors dominating the joint shear behaviour have been investigated for decades (Phien-wej et al 1990;de Toledo and de Freitas 1993;Indraratna et al 2001Indraratna et al , 2010, however the influence of infill saturation/water condition has not been recognised until recently (Alonso et al 2013;Indraratna et al 2014;Khosravi et al 2016).…”
Section: Introductionmentioning
confidence: 99%